Impact of telecommunication network shutdown on academic performance of students, Federal University Dutsin-Ma, Katsina State, Nigeria - Yakubu, Hajara; Danzangi, Sirajo Abubakar; Manjack, Felix Usman (Communicate: Journal of Library and Information Science, 2025)
This study examines the impact of telecommunication network shutdowns on the academic performance of students at Federal University Dutsin-Ma (FUDMA) in Katsina State, Nigeria. Network access is integral for students’ academic activities, enabling them to complete assignments, download resources, and communicate with faculty and peers. However, in response to security concerns, the government imposed a network shutdown in Dutsin-Ma, severely disrupting students’ ability to perform these tasks. This research explores the consequences of the shutdown, the alternative methods students employed to access network services, and the challenges they faced. Data was gathered through a survey of final-year students, with findings indicating that network disruptions led to missed deadlines, difficulties in remote learning, and heightened communication challenges. The study highlights the adverse effects of network shutdowns on students’ academic progress and calls for alternative security measures that do not compromise students’ access to essential digital resources.